Sciences and audiences along the lastcentury: the impact of Astronomy Education - Barros, Rosario Magdalena (2020)
Just as in the past, the development of the natural sciences and in particular of astronomy has changed the history of humanity. If we think about the role of our discipline into the future, it shows its enormous power in the field of education, owing to the possibility of awakening interest in science in very varied audiences. Within the framework of the enormous progress made in the technologies related to astronomy, many of them of daily use, the role of the astronomer in the era of Communications acquires fundamental importance. In this presentation, we will try to make a journey through the different ways of presenting astronomical topics for different audiences over the last 100 years. In turn, we will show some specific achievements, associated with education programmes of the discipline. We discuss the impact produced by proposals that are both rigorous in terms of content, and also appeal to the development of the human being in an integral manner, within the framework of citizen science activities. For this research, we have taken into account the uninterrupted development of the NASE programme, which has performed 112 courses in 24 countries throughout the world and in different languages. NASE has involved 4966 secondary teachers in the last eight years.